Penerapan Metode Tahsin dalam Meningkatkan Keaktifan dan Kemampuan Membaca Al-Qur’an Siswa Madrasah Ibtidaiyah - Ulfi Wisa Belinda (Ma'had Aly Idrisiyyah, 2023)
This research was motivated bythe lack of activity and ability to read theAl-Qur’anin class 1 students of Madrasah Ibtidaiyah Al-Islam Bengkulu City. Most students have not been able to read hijaiyah letters properly and correctly in accordance with the rules for the accuracy of the makharijul letters and the accuracy of their tajwid as targets set in basic competencies and competency standards. This study aims, firstly to determine the activity of students in learning the Qur'an by applying the Tahsin learning method in Class I Madrasah Ibtidaiyah Al-Islam Bengkulu City. The second is to find out the students' ability to read the Koran by applying the Tahsin learning method in class I Madrasah Ibtidaiyah Al-Islam Bengkulu City. This type of research is classroom action research or classroom action research. The results of this study indicate an increase in the activity and ability to read the Qur'an for grade 1 Madrasah Ibtidaiyah students after applying the Tahsin method so that students experience an increase in their abilities because it is accompanied by an increase in activity, this can be seen from the data on student test results in cycle I there is an average increase -the student average was from 60.25 in cycle I increased to 65.12 in cycle II and increased again in cycle III with an average student score of 79.87%. Meanwhile, the percentage of classical learning completeness also increased, from 25% in cycle I to 65% in cycle II and even more to 100% in cycle III. Penelitian ini dilatarbelakangi oleh kurangnya keaktifan dan kemampuan membaca Al-Qur’an Siswa kelas 1 Madrasah Ibtidaiyah Al-Islam Kota Bengkulu. Sebagian besar siswa belum mampu membaca huruf hijaiyah secara baik dan benar sesuai dengan kaidah ketepatan makharijul huruf dan ketepatan tajwidnya sebagaimana target yang telah ditetapkan dalam kompetensi dasar dan standar kompetensi. Penelitian ini bertujuan, pertama untuk mengetahui keaktifan siswa dalam pembelajaran al-Qur’an dengan menerapkan metode pembelajaran Tahsin di Kelas I Madrasah Ibtidaiyah Al-Islam Kota Bengkulu. Kedua untuk mengetahui kemampuan membaca al-Qur’an siswa denganmenerapkan metode pembelajaran Tahsin di kelas I Madrasah Ibtidaiyah Al-Islam Kota Bengkulu.Jenis penelitian iniadalah classroom action researchatau penelitian tindakan kelas. Hasil penelitian ini menunjukkan adanya peningkatan keaktifan dan kemampuan membaca Al-Qur’an Siswa kelas 1 Madrasah Ibtidaiyah setelah diterapkan metode Tahsin sehingga siswa mengalami peningkatan dibidang kemampuannya karena disertai dengan peningkatan keaktifan, hal ini terlihat dari data hasil tes siswa pada siklus I terjadi peningkatan rata-rata siswa yaitu dari 60,25 pada siklus I meningkat menjadi 65,12 pada siklus II dan meningkat lagi pada siklus III dengan nilai rata-rata siswa 79,87%. Sedangkan pada persentase ketuntasan belajar secara klasikal juga terjadi peningkatan yaitu dari 25% pada siklus I meningkat menjadi 65% pada siklus II dan lebih meningkat lagi menjadi 100% pada siklus III.